Interprofessional education: the attitude among students of health science bachelor's degree programmes at universities of applied sciences in Austria / Interprofessionelle Ausbildung: Die Einstellung der Studierenden gesundheitswissenschaftlicher Bachelor-Studiengänge an österreichischen Fachhochschulen - Kühteubl Monika; Pekar Thomas (Sciendo, 2023)
Interprofessional collaboration is a strategy to meet the challenges of increasing complexity in the health system. The basis for cooperation in professional life must already be established in the context of interprofessional education (IPE). Students' attitude towards IPE is a crucial factor in the development of interprofessional competences.